2021
DOI: 10.1111/jth.15529
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation assays are versatile tools in blood coagulation analysis: A review of technical features, and applications from research to laboratory routine

Abstract: Thrombin is the pivotal enzyme in the biochemistry of secondary hemostasis crucial to maintaining homeostasis of hemostasis. In contrast to routine coagulation tests (PT or aPTT) or procoagulant or anticoagulant factor assays (e.g. fibrinogen, factor VIII, antithrombin or protein C), the thrombin generation assay (TGA), also named thrombin generation test (TGT) is a so‐called “global assay” that provides a picture of the hemostasis balance though a continuous and simultaneous measurement of thrombin formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 68 publications
0
49
0
5
Order By: Relevance
“…This resulted in a significantly reduced interlaboratory variability 96 . For further information on the technical limitations in standardization issues of TGA see Depasse 2021 97 . However, TGA may still benefit from standardization across different systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in a significantly reduced interlaboratory variability 96 . For further information on the technical limitations in standardization issues of TGA see Depasse 2021 97 . However, TGA may still benefit from standardization across different systems.…”
Section: Discussionmentioning
confidence: 99%
“…96 For further information on the technical limitations in standardization issues of TGA see Depasse 2021 . 97 However, TGA may still benefit from standardization across different systems. One should keep in mind that, in contrast to TGA, some very common routine assays such as aPTT which are considered to give reliable readouts equally lack standardization.…”
Section: Discussionmentioning
confidence: 99%
“…TGAs measure thrombin formation in plasma after addition of tissue factor and phospholipids. Contrarily to classical coagulation assays, both procoagulant and anticoagulant processes are dynamically investigated, resulting in a thrombogram with multiple derivate parameters reported [108]. TGAs can be used to assess hypo-and hypercoagulability, including APS [109,110].…”
Section: Alternative Assays For Lac Measurementmentioning
confidence: 99%
“…Recently, automated systems were introduced on the market with higher potential of use in routine practice because of reduced laboratory technician hands-on time, and decrease in inter-laboratory variation. Automated TGAs may provide more information based on phospholipid-dependent testing in one assay, compared to the multitude of assays needed for LAC detection today [108].…”
Section: Alternative Assays For Lac Measurementmentioning
confidence: 99%
“…The risk of bleeding or thrombosis can be assessed based on TGA testing. Based on an analysis of the literature, Tripodi et al concluded that TGA is a promising laboratory tool for investigating bleeding coagulopathies and predicting the risk of recurrent venous thromboembolism [ 69 , 70 ]. Similarly, Binder et al document in their review article most of the clinical applications of TGA for the prediction of thrombosis [ 71 ].…”
Section: Methodsmentioning
confidence: 99%